Including maritime transport in the EU's climate change policy: Country-based allocation and effects - Nadine Heitmann (Kiel Institute for the World Economy (IfW), 2013)
The European Union (EU) is actively campaigning for the global regulation of carbon emissions generated by maritime bunker fuels because these emissions are presently barely regulated and are projected to increase significantly in the coming decades. However, since a global regulation has not been reached yet, the EU is seeking ways to include the shipping sector in its greenhouse gas reduction commitment for 2020. In this paper, we look at the effect of including the shipping sector's emissions in the EU reduction commitment that is based on the nationality of a ship. Emissions that are generated by ships owned, operated or flagged by the 27 EU countries are allocated to the EU total GHG emissions. We first analyse the effects on the reduction commitment caused by the three allocations. We then use marginal abatement cost curves (MACCs) in order to determine how much the shipping sector of the 27 EU countries, defined by the three allocations, could contribute efficiently to a total given emission reduction target for all sectors in the EU. Moreover, we use MACCs in order to determine if some country fleets could reduce emissions in the shipping sector relatively more efficiently than other countries under a given emission reduction target for all sectors. Our findings indicate that the shipping sector could contribute efficiently to the EU's emission reductions by up to 8.5%. Since the composition of the individual country fleets and applied measures are similar across countries, their individual reductions relative to their fleet-specific business-as-usual (BAU) emissions are on average the same.
Keywords: Q52; Q54; Q58; 330; EU; climate change; shipping sector; CO2 emissions; marginal abatement cost curve